The Effect of Resistance Training on the Function after Hip Replacement: A Meta-analysis of Randomized Controlled Trials - Chen, Langxin; Chen, Guanlin (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Introduction The efficacy of resistance training for hip replacement remains controversial. We conducted a systematic review and meta-analysis to explore the influence of resistance training on functional recovery for hip replacement.Methods We searched PubMed, EMbase, Web of Science, EBSCO, and Cochrane Library databases through April 2018 for randomized controlled trials (RCTs) assessing the effect of resistance training on hip replacement.Results Five RCTs involving 251 patients are included in the meta-analysis. Overall, compared with the control group for post-hip replacement patients, resistance training can significantly improve hip-related quality of life (standard mean difference [SMD] = 0.35; 95% CI = 0.02 to 0.68; p = 0.04), symptoms (SMD = 0.41; 95% CI = 0.08 to 0.74; p = 0.02), sports and recreation (SMD = 0.41; 95% CI = 0.08 to 0.75; p = 0.01), and reduce pain scores (SMD = 0.41; 95% CI = 0.08 to 0.74; p = 0.02), but has no remarkable impact on activities of daily living function (SMD = 0.48; 95% CI = 0 to 0.96; p = 0.05), sit to stand (SMD = 0.17; 95% CI = − 0.25 to 0.59; p = 0.44), stair climb performance (SMD = 0.06; 95% CI = − 0.36 to 0.48; p = 0.77), and leg extension power (SMD = 0.42; 95% CI = − 0.17 to 1.01; p = 0.17).Conclusions Resistance training is associated with significantly improved hip-related quality of life, symptoms, and sports and recreation, and decreased pain scores in post-hip replacement patients.
Keywords: resistance training; hip replacement; functional recovery